Intelligent power transformer protection relay based fuzzy logic - Hamed Ahmed, Abdullah; Jasim Sultan, Ahmed (International Journal of Engineering and Technology, 2018)
The main issue of differential relay is to sense the varying of power transformer current during any working conditions. . Recently, the im-provement of core steel decreases the 2nd harmonic of current in inrush state, but that will produce maloperation of relay in the case of low second harmonic inrush current and in the case of high second harmonic internal fault. The fuzzy based differential relay is used for power transformer protection which consists of harmonic restraint, flux-differential current derivative curve and percentage differential characteris-tic curve. The proposed approach was implemented in MATLAB /Simulink (R2010B) environment. Numerical results obtained have veri-fied the effectiveness of the proposed scheme when tested for all fault types